Speed lights! - Mangual, C. Ines; Dynamo Limited; Nickelodeon (Television network) (New York Random House, 2016)
Blaze and his monster truck friends enjoy racing at night until someone steals all the lights, and it is up to Blaze to capture the Light Thief
At head of title: Nickelodeon Blaze and the monster machines
English Stories
Keywords: Monster trucks -- Fiction; Robbers and outlaws -- Fiction; Truck racing -- Fiction